Cervical Myelopathy Caused by Engorgement of the Epidural Venous Plexus due to Cerebrospinal Fluid Overdrainage: Case Report and Review of the Literature - Dantas, Fernando Luiz Rolemberg; Dantas, François; Raso, Jair Leopoldo; Barroso, Pedro Moreira Coelho (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2016)
This is a case report of a 33-year-old woman with cervical myelopathy caused by an enlargement of the cervical venous plexus, after she was submitted to a ventriculoperitoneal (VP) shunt that evolved to overdrainage.Magnetic Resonance Imaging (MRI) revealed an epidural venous enlargement within the spinal channel, with a 50% narrowing from C2 to C5, and spinal cord compression. A shunt revision was performed using a programmable drainage system, and a second MRI revealed the absence of the venous enlargement, resulting in cervical spinal cord decompression and remission of neurological symptoms.Compressive myelopathy consequent to the enlargement of the epidural venous plexus related to the overdrainage of the ventriculoperitoneal shunt system without typical signs of intracranial hypotension may result in misleading etiological diagnoses. Acknowledging this disorder is important to distinguish it from neoplastic processes or hematomas, for which surgical intervention may be needed.
Keywords: overdrainage; spinal dural enhancement; ventriculoperitoneal shunt; cervical myelopathy; vertebral venous system; craniocervical junction